A monometallic lanthanide bis(methanediide) single molecule magnet with a large energy barrier and complex spin relaxation behaviour. Issue 1 (1st December 2015) - Gregson, Matthew; Chilton, Nicholas F.; Ariciu, Ana-Maria; Tuna, Floriana; Crowe, Iain F.; Lewis, William; Blake, Alexander J.; Collison, David; McInnes, Eric J. L.; Winpenny, Richard E. P.; Liddle, Stephen T.
Abstract : We report a monometallic dysprosium(iii ) single molecule magnet with record energy barriers and unusual spin relaxation behaviour. Abstract : We report a dysprosium(iii ) bis(methanediide) single molecule magnet (SMM) where stabilisation of the highly magnetic states and suppression of mixing of opposite magnetic projections is imposed by a linear arrangement of negatively-charged donor atoms supported by weak neutral donors. Treatment of [Ln(BIPM TMS )(BIPM TMS H)] [Ln = Dy, 1Dy ; Y, 1Y ; BIPM TMS = {C(PPh2 NSiMe3 )2 } 2− ; BIPM TMS H = {HC(PPh2 NSiMe3 )2 } − ] with benzyl potassium/18-crown-6 ether (18C6) in THF afforded [Ln(BIPM TMS )2 ][K(18C6)(THF)2 ] [Ln = Dy, 2Dy ; Y, 2Y ]. AC magnetic measurements of2Dy in zero DC field show temperature- and frequency-dependent SMM behaviour. Orbach relaxation dominates at high temperature, but at lower temperatures a second-order Raman process dominates. Complex2Dy exhibits two thermally activated energy barriers ( U eff ) of 721 and 813 K, the largest U eff values for any monometallic dysprosium(iii ) complex. Dilution experiments confirm the molecular origin of this phenomenon. Complex2Dy has rich magnetic dynamics; field-cooled (FC)/zero-field cooled (ZFC) susceptibility measurements show a clear divergence at 16 K, meaning the magnetic observables are out-of-equilibrium below this temperature, however the maximum in ZFC, which conventionally defines the blocking temperature, T B, is found at 10 K. Magnetic hysteresis is also observed in 10%2Dy @2Y at these temperatures. Ab initio calculations suggest the lowest three Kramers doublets of the ground 6 H15/2 multiplet of2Dy are essentially pure, well-isolated |±15/2〉, |±13/2〉 and |±11/2〉 states quantised along the CDyC axis. Thermal relaxation occurs via the 4 th and 5 th doublets, verified experimentally for the first time, and calculated U eff values of 742 and 810 K compare very well to experimental magnetism and luminescence data. This work validates a design strategy towards realising high-temperature SMMs and produces unusual spin relaxation behaviour where the magnetic observables are out-of-equilibrium some 6 K above the formal blocking temperature.